2002
DOI: 10.3168/jds.s0022-0302(02)74259-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zeolite A Supplementation in the Dry Period on Periparturient Calcium, Phosphorus, and Magnesium Homeostasis

Abstract: One potential way of preventing parturient hypocalcemia in the dairy cow is to feed dry cow rations very low in calcium (<20 g/d); but, because it is difficult to formulate rations sufficiently low in calcium, this principle has been almost abandoned. Recent studies have shown, however, that it is possible to prevent milk fever, as well as subclinical hypocalcemia, by supplementing the dry cow ration with sodium aluminium silicate (zeolite A), which has the capacity to bind calcium. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
65
2
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 30 publications
16
65
2
9
Order By: Relevance
“…Sodium zeolite A (SZA) is an aluminosilicate that is hydrolyzed at low pH into silicic acid, amorphous aluminum silicates and aluminum [1]. Thus, by supplying SZA to the diet, an animal's gastrointestinal tract can break down this zeolite into orthosilicic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium zeolite A (SZA) is an aluminosilicate that is hydrolyzed at low pH into silicic acid, amorphous aluminum silicates and aluminum [1]. Thus, by supplying SZA to the diet, an animal's gastrointestinal tract can break down this zeolite into orthosilicic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium zeolite A (SZA) is an aluminosilicate that is hydrolyzed at low pH into silicic acid, amorphous aluminum silicates, and aluminum [1]. Thus, by supplying SZA to the diet, an animal's gastrointestinal tract can break down the zeolite into orthosilicic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies aimed at the reduction of Ca availability by adding the synthetic sodium aluminosilicate zeolite A to bind dietary Ca have been performed. In several studies, it has been shown that zeolite A supplementation during late gestation stabilizes blood Ca concentrations around parturition (Thilsing-Hansen and Jorgensen 2001;Thilsing-Hansen et al, 2002;Pallesen et al, 2008;Grabherr et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, additional effects of zeolite A on plasma P (Enemark et al, 2003;Pallesen et al, 2008) and Mg (Thilsing-Hansen et al, 2002;Grabherr et al, 2009) as well as on urinary pH and renal excretion of minerals (Thilsing-Hansen et al, 2002) were also reported. Thus, the impact of zeolite A on mineral homeostasis appears more complex than just reducing the availability of Ca in the ration.…”
Section: Introductionmentioning
confidence: 99%